Intraventricular ganglioglioma with unusual location and morphology-A case report - Mugdha Kamat Timble; Aruna Patil; Arun L Naik; Swarna Shivakumar; Bhushan Chaudhary (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2020)
Ganglioglioma is one of the common tumour responsible for refractory temporal lobe epilepsy in children and young adults. Positioned in the group glioneural tumours, it is mostly of low grade histology. Here we outline a rare case of intraventricular ganglioglioma at atypical location with atypical morphology, lacking its most classical symptom of epilepsy.